Analisis Pengaruh Murabahah, Mudharabah, Musyarakah, FDR, NPF dan BOPO Terhadap Kinerja Perbankan Syariah Tahun 2011-2020 - Novitasari Primadita (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to examine the effect of buying and selling financing, profit-sharing financing, FDR, NPF, and OEOI on Islamic Banking Performance as proxied by the ROA ratio. Sources of data in this study are secondary data on Islamic banking statistics taken from the Financial Services Authority website. The research data is in the form of time series data from January 2011 to August 2020. The analysis technique uses the ECM (Error Correction Model). The results showed that murabahah, mudharabah, and musyarakah financing had no effect in the short term on ROA, while in the long term only the mudharabah financing variable had a positive and significant effect on the 10% degree on ROA BUS, for murabahah and musyarakah financing variables had no effect on ROA has no effect in the long term. The NPF and BOPO variables have a short-term effect on ROA while FDR has no effect on ROA in the short term. In the long run, the variables FDR, NPF, and BOPO have an effect on ROA. Keywords: ROA, Murabahah, Mudharabah, Musyarakah, FDR, NPF, and BOPO